2015
DOI: 10.1517/17425247.2015.1043125
|View full text |Cite
|
Sign up to set email alerts
|

A first step toward liposome-mediated intracellular bacteriophage therapy

Abstract: These are important milestones in the development of an intracellular bacteriophage therapy that might be useful in the fight against multi-drug-resistant intracellular pathogens like Mycobacterium tuberculosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 50 publications
0
57
0
Order By: Relevance
“…Recent studies have investigated the effect of experimental phage therapy on intracellular killing of bacteria in patients' peripheral blood monocytes, polymorphonuclear neutrophils, and murine macrophages (3-6). We set out to study the intracellular killing potential of such lytic phages in nonprofessional phagocytic cells (7,8). We investigated this question using phage vB_SauM_JS25, a broad-spectrum virulent phage belonging to the family Myoviridae (9).…”
Section: Abstract Mac-t Cells Staphylococcus Aureus Bacteriophagesmentioning
confidence: 99%
“…Recent studies have investigated the effect of experimental phage therapy on intracellular killing of bacteria in patients' peripheral blood monocytes, polymorphonuclear neutrophils, and murine macrophages (3-6). We set out to study the intracellular killing potential of such lytic phages in nonprofessional phagocytic cells (7,8). We investigated this question using phage vB_SauM_JS25, a broad-spectrum virulent phage belonging to the family Myoviridae (9).…”
Section: Abstract Mac-t Cells Staphylococcus Aureus Bacteriophagesmentioning
confidence: 99%
“…2,3 Alternatively, hydrogel-assisted swelling facilitated construction of vesicles under physiological conditions with various lipid compositions. 8,15 The technique has since expanded the possibility to study complex lipid-protein interactions, 16,17 vesicles for applications in drug delivery 18 and use of vesicles as micro-reactors. 19,20 However no studies have reported multicompartment formation in vesicles using this methodology.…”
Section: Introductionmentioning
confidence: 99%
“…P‐glycoprotein carries a role in crossing the blood‐brain barriers and in the uptake into cancer cells. GUVs formed using the gel‐assisted hydration could be used for medical purposes such as delivering bacteriophages to cells to fight again antibiotic‐resistant bacteria . Bacteriophages cannot penetrate cells but by encapsulating bacteriophages in liposomes GUVs, they could be delivered to eukaryotic cells.…”
Section: Gel‐assisted Hydrationmentioning
confidence: 99%